2022
DOI: 10.1186/s12866-022-02687-8
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the MSTN gene expression changes the composition and function of the gut microbiome in sheep

Abstract: Background Myostatin (MSTN) negatively regulates the muscle growth in animals and MSTN deficient sheep have been widely reported previously. The goal of this study was to explore how MSTN inactivation influences their gut microbiota composition and potential functions. Results We compared the slaughter parameters and meat quality of 3 MSTN-edited male sheep and 3 wild-type male sheep, and analyzed the gut microbiome of the MSTN-edited sheep (8 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Moreover, main meat quality characteristics, including pH, drip loss, intramuscular fat, crude protein, and shearing force of gluteal muscles, did not show changes between the MSTN -edited and WT lambs . A more recent investigation showed that the body weight, carcass weight, and eye muscle area of MSTN -edited sheep were significantly higher than those of WT sheep, with no significant differences in the meat quality indexes . Additionally, targeting the MSTN gene could induce changes in the composition and function of the gut microbiome between the MSTN -edited and WT sheep …”
Section: Targeting the Mstn Gene In Sheepmentioning
confidence: 96%
See 3 more Smart Citations
“…Moreover, main meat quality characteristics, including pH, drip loss, intramuscular fat, crude protein, and shearing force of gluteal muscles, did not show changes between the MSTN -edited and WT lambs . A more recent investigation showed that the body weight, carcass weight, and eye muscle area of MSTN -edited sheep were significantly higher than those of WT sheep, with no significant differences in the meat quality indexes . Additionally, targeting the MSTN gene could induce changes in the composition and function of the gut microbiome between the MSTN -edited and WT sheep …”
Section: Targeting the Mstn Gene In Sheepmentioning
confidence: 96%
“…114 Additionally, targeting the MSTN gene could induce changes in the composition and function of the gut microbiome between the MSTN-edited and WT sheep. 114 The MSTN multiplex edited sheep were also utilized to assess potential off-target activities and to comprehensively analyze the sequence data for de novo single nucleotide variants (SNVs), small insertions and deletions (Indels), and structural variations (SVs) at the genomic level. 115 The trio-based sequencing approach revealed a low incidence of SNVs and Indels and almost negligible off-target modifications.…”
Section: ■ Targeting the Mstn Gene In Sheepmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, cattle with myostatin gene mutation which negatively regulates muscle development was shown to affect the metabolism of Ruminococcaceae_UCG-013 , Clostridium_sensu_stricto_1 and Ruminococcaceae_UCG-010 in the gut [ 40 ]. Myostatin-edited sheep increased abundance of Firmicutes , whereas decreased abundance of Bacteroidota [ 41 ], suggesting that muscle development and gut microbiota are closely involved.…”
Section: Recent Research On Lower Gut Microbiome Contributing To Meat...mentioning
confidence: 99%